MyoAnalyst: an ImageJ plugin for accurate and automatic myofiber segmentation and analysis in skeletal muscle cross sections. - Zhang, Bao; Wang, Shuaiyu; Wang, Yaning; Liang, Chen; Zhang, Hongbo (Histochemistry & Cell Biology, 2025)
Quantifying myofiber size is essential for assessing the health and function of skeletal muscle. Although several ImageJ plugins are currently available for myofiber segmentation and size quantification, significant challenges remain—most notably limited accuracy and poor compatibility with hematoxylin and eosin (H&E)-stained skeletal muscle cross sections. In this study, we introduce MyoAnalyst, an ImageJ plugin designed to enable automated analysis of both immunofluorescence (IF)- and H&E-stained skeletal muscle cross sections. Compared to existing ImageJ plugins, MyoAnalyst delivers enhanced segmentation sensitivity and superior boundary delineation accuracy across both healthy and injured muscle tissue stained with IF. Importantly, it also supports fully automated analysis of H&E-stained sections. With its intuitive graphical interface and batch processing capabilities, MyoAnalyst provides a potentially efficient tool for myofiber size quantification in both research and clinical settings.